Prevalence of THRB Gene Mutations in Misan Province Thyroidism Patients: Prevalensi Mutasi Gen THRB pada Pasien Tiroid di Provinsi Misan - Al-Taie, Duha T.; Jumaa, Zahr'aa Kateb; Husain, Rehal Jehad; Rahi, Eman H. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Thyroid disorders such as hypothyroidism and hyperthyroidism are common endocrine abnormalities characterized by disrupted levels of triiodothyronine (T3), thyroxine (T4), and thyroid-stimulating hormone (TSH). Specific Background: Mutations in the thyroid hormone receptor beta (THRB) gene are implicated in thyroid hormone resistance syndromes and potentially in other thyroid dysfunctions. Knowledge Gap: However, there is limited data regarding the prevalence of THRB gene mutations among thyroid disorder patients in Misan Province, Iraq. Aims: This study aimed to evaluate the presence of THRB gene mutations among women diagnosed with thyroid disorders and assess corresponding hormonal variations across age groups. Results: Hormonal analysis revealed significant deviations in FT3, FT4, and TSH levels in both hypothyroid and hyperthyroid patients across multiple age groups. Molecular analysis, however, did not detect any pathogenic mutations in the THRB gene. Novelty: Despite the identification of several unique haplotypes among patients, none corresponded to known pathogenic mutations, suggesting possible population-specific genetic profiles without direct impact on receptor function. Implications: These findings underscore the need for broader genetic screening beyond THRB in diagnosing thyroid disorders and highlight the limited role of THRB mutations in the pathogenesis of thyroid dysfunction in this regional cohort.Highlight : No mutations were found in the THRB gene in patients with hypothyroidism and hyperthyroidism. Hormone analysis showed significant differences in FT3, FT4, and TSH levels between age groups. There were ten varying THRB gene haplotypes, but no mutations were detected. Keywords : Thyroid disorders, Thyroid hormone, TRHB gene, Novel mutation, Hyperthyroidism